(untitled) (Journal of the College of Basic Education, 2022)
The textual space makes the reader active in the novel, as he stands on the lengths of the fictional work, trying to probe the depths of the text. This concept has taken its way in modern critical studies because it represents a group of factors that revolve around one point in terms of literary work. It is generated in the text through the space occupied by writing as typographical characters on the paper space, and the text space includes the cover design, the selection of the title, the dedication, the export, etc., etc., and according to all of that, the textual space is monitored by the writer’s only point of view, which dominates in a way Or another on the whole of the discourse so that the entire text gathers in one point and all the lines gather in the depth where the writer resides.